From spectral measurement to softening trajectory prediction: Integrating spatially resolved spectroscopy with kinetic modeling in Kiwifruit - Xuejian Zhou; Bin Li; Tetsuya Inagaki; Satoru Tsuchikawa; Te Ma (Postharvest Biology and Technology, 2026)

A data-driven framework for effective single-group cross section adjustment in point-depletion burnup calculations - Wei-Jia Meng; Te Sheng; Ou-Yi Li; Gang-Lin Yu (Annals of Nuclear Energy, 2026)

Collision avoidance for unmanned surface vehicle in busy waterways based on improved DDPG and IMMKF - Te Lian; Qijun Liu; Defeng Wu; Yuqin Li; Chunxin Tian (Ocean Engineering, 2026)

An AB2X5-type oxidizer by multi-ionic assembly for high-energy solid propellants - Hongyu Lv; Xiaoyu Feng; Xin Li; Te Ning; Hui Li; Wen Ao; Hongqi Nie; Siwei Song; Yi Wang; Qinghua Zhang (Chemical Engineering Journal, 2026)

Real-world onboard evaluation of exhaust aftertreatment effects on particle-bound persistent free radicals and reactive oxygen species generation potential from inland vessels - Yu-Chieh Wang; Wei-Min Ching; Hsi-Hsien Yang; Yen-Hsien Li; Tzu-Hsien Tseng; Hsin-Te Yu (Environmental Pollution, 2026)

UAV-based phenotyping estimation for precision variable-rate application of growth regulator in cotton production - Te Zhang; Xin Du; Yukun Wang; Qinghua Liao; Chenyu Xiao; Qiangzi Li; Dongyong Xu; Mingwei Du; Xiaoli Tian; Zhaohu Li (Field Crops Research, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

Deep reinforcement learning for long-horizon reservoir operation: Temporal horizon, state representation, and hydrological data synthesis - Zaichao Xie; Minglei Ren; Wei Xu; Te Zhang; Bing Zhu; Dong Li; Shuncai Zhang; Junbo Wang (Journal of Hydrology, 2026)

The characteristics and differences of raindrop size distribution in three typhoon rainstorm events in Suzhou, Jiangsu - Wei Sun; Jialu Sun; Te Li; Xiaoran Zhuang (Meteorology and Atmospheric Physics, 2026)

First complete coding sequence of ovine herpesvirus 2 from a malignant catarrhal fever case of Formosan sambar deer in Taiwan: Genomic characterization and molecular epidemiology - Ruei-Sheng Tsai; Shih-Te Chuang; Hau-You Tzeng; Fong-Yuan Lin; Ching-Yu Tseng; Yi-Chen Chen; Wei-Li Hsu (The Veterinary Journal, 2026)

Integrating satellite-derived land cover and remote sensing variables into land use regression for urban PM2.5 estimation - Shih-Ya Wang; Tzu-Chi Lin; Hsueh-Hsun Li; Chao-Hsu Yang; Pei-Te Chiueh (Atmospheric Environment, 2026)

A digital microfluidics-based single-cell ddPCR platform for high-throughput gene copy number analysis applied to single cultured cells - Yicheng Sun; Jiancong Liang; Hui Li; Yechen Fan; Te Peng; Siyi Hu; Yuan Gao; Wenli Zhao; Ling Jiang; Khadija Urooj; Hanbin Ma; Mude Shi; et al. (Analytica Chimica Acta, 2026)

Dang-Gui-Bu-Xue-Tang triggers GM-CSF and IL-4 secretion corporated with increased amount of Immunoglobulins - Sheng-Teng Huang; Jia-Hau Yen; Yu-Chun Lin; Ming-Ching Kao; Chia-Ju Chuang; Shu-Tuan Chiang; Te-Mao Li (Advances in Traditional Medicine, 2026)

Robust reconstruction of seamless daily VIIRS nighttime light imagery with cloud mask refinement and multi-strategy spatiotemporal gap-filling - Qiming Zheng; Te Mu; Xiaolin Zhu; Xiaoyue Tan; Yuyu Zhou; Jiajun Li; Sylvia Y. He (Remote Sensing of Environment, 2026)

Corrigendum to “Red-emitting carbon dots as highly sensitive fluorescent probes for detecting changes of ClO- in inflammatory systems and cell pyroptosis” [Journal of Photochemistry & Photobiology, B: Biology 276 (2026) 113371] - Jing Li; Xiuying Li; Liya Wu; Huiying Lv; Te Liu; Hua Yao; Jinlan Jiang (Journal of Photochemistry and Photobiology B: Biology, 2026)

Retrieval of cotton defoliation rate using random forest model based on rate of vegetation index change - Yukun Wang; Chenyu Xiao; Te Zhang; Xinghua Yu; Yao Wang; Yunxin Xu; Fangjun Li; Sumei Wan; Guodong Chen; Xiaoli Tian; Xin Du; Mingwei Du; et al. (European Journal of Agronomy, 2026)

Precursor engineering via multifunctional additive for modulating perovskite crystallization and interface passivation enabled high-performance perovskite solar cells over 26% - Zhenye Liang; Chen Tian; Zhenhuang Su; Te Ji; Zhengwu Liu; Kunming Hou; Yulin Qin; Lianjie Ma; Junxiang Chen; Lingling Guo; Luozhen Jiang; Meng Du; et al. (Chemical Engineering Journal, 2026)

Ambient fine particulate matter, constituents, and ischemic heart disease mortality: a time-stratified case-crossover analysis in Central China - Ling-Shuang Lv; Xiu-Ying Liu; Yuan Liu; Zi-Tong Zhuang; Xin-Ye Zhang; Yue-Hua Hu; Ji Hu; Te-Hui Zeng; Li-Dong Gao; Xin Xia; Li Yin (Air Quality, Atmosphere & Health, 2026)

Lake Water Depth and Nutrient Gradients Mediate Aquatic Plant Distribution via the Strength of Trait Network Associations - Guixiang Yuan; Huan Long; Jun Liu; Qiling Xie; Yaoxuan Tan; Zihui Hong; Jiahui Yue; Aimin Zhou; Hexuan Zhou; Weilin Xu; Bao Wang; Huanyao Liu; et al. (Global Change Biology, 2026)
Aquatic macrophyte responses and adaptation to water depth and nutrient gradients are of critical importance for understanding the functional ecology of lakes and their restoration when degraded. However, the role of plant trait networks (PTNs), a powerful tool for decoding trait–environment–function relationships, in mediating these adaptations remains unclear, particularly across species and community scales. We conducted cross‐scale PTN analyses at species and community levels for aquatic macrophytes, integrating assessments of phylogenetic signals and hierarchical environmental filtering. At species level, aquatic macrophytes exhibited two complementary PTN‐based adaptive strategies: trait compartmentalization to enhance stress tolerance and trait integration to optimize resource utilization. Notably, local environmental conditions (rather than phylogenetic signals) dominated the pattern of PTN metrics, highlighting the primacy of immediate habitat constraints over evolutionary relatedness in driving species‐specific adaptations. At community level, environmental filtering operated hierarchically, acting sequentially by water depth, nutrient availability, and lake morphology. PTNs further mediated the trade‐off between community diversity and productivity, providing a mechanistic link between abiotic filtering and ecosystem function. Our findings advance network theory in functional ecology by extending its application to aquatic systems, bridging longstanding gaps between terrestrial and aquatic PTN research, and offering actionable guidance for eutrophic lake restoration (e.g., by targeting PTN‐linked core traits related to nutrient adaptation). Overall, our work provides a cross‐scale framework for understanding PTN mediated adaptation of aquatic macrophytes and its implications for ecosystem management.

Red-emitting carbon dots as highly sensitive fluorescent probes for detecting changes of ClO−in inflammatory systems and cell pyroptosis - Jing Li; Xiuying Li; Liya Wu; Huiying Lv; Te Liu; Hua Yao; Jinlan Jiang (Journal of Photochemistry and Photobiology B: Biology, 2026)

Critical coverage thresholds of submerged macrophytes for phosphorus pulse mitigation and resilience enhancement in shallow lakes - Zheng Li; Qingchuan Chou; Hang Shan; Yuqing Tian; Kuanyi Li; Haojie Su; Te Cao; Chaochao Lv (Journal of Environmental Management, 2026)

Lentipes ptasan , a new species of sicydiine goby (Teleostei: Gobioidei) from the Western Pacific, with a redescription of L. mindanaoensis - Wei‐Cheng Jhuang; Cleto L. Nañola; Xiao Fei Li; Te‐Yu Liao (Journal of Fish Biology, 2026)
Lentipes ptasan sp. nov. is described based on specimens collected from Taiwan and Mindanao Island. It is a large‐sized Lentipes species distinguished by several male‐specific characteristics, including an upper lip protruding beyond snout obviously, fewer premaxillary tricuspid teeth, two black lines running from the front of the eye through the nostrils to the tip of the snout, a wide brown longitudinal band at the base of the anal fin, and the distinctive nuptial coloration featuring a brown vertical band extending from back to belly on the middle of the body. The complex distribution of Lentipes species and their genetic differentiation may be influenced by sexual selection, historical biogeographic events and contemporary ecological processes. However, due to the recent divergence of Lentipes species, 11 out of 14 species could not be distinguished by the cytochrome oxidase subunit I gene. Furthermore, Lentipes mindanaoensis is redescribed, with L. adelphizonus treated as its junior synonym.

Construction of a risk model based on exosome-related genes predict clinical prognosis and therapeutic response and revealing TIMP1 as a promising target in colorectal cancer - Xinyu Gao; Te Zhang; Tianhao Li; Yongdan Zhang; Xipeng Zhang; Haoren Jing (Human Cell, 2026)

Deep learning-based optimal adaptive regulation pathway of algal blooms in urban rivers under long-term uncertainties - Changqing Xu; Tianyu Jia; Te Xu; Yuqiao Lan; Nan Li; Haifeng Jia (Water Research, 2026)

Collision avoidance for maritime autonomous surface ship in busy waterways based on the improved deep reinforcement learning and K-means clustering - Hui Yu; Defeng Wu; Guoqiang Li; Te Lian; Yuqin Li; Fusheng Li (Ocean Engineering, 2026)

Molecular-scale insights into the freeze-thaw process of aqueous and saline solutions in hydrated‑calcium-silicate gel pores - Jiachuan Ran; Yuanming Lai; Mingyi Zhang; Fan Yu; Te Liang; Wansheng Pei; Hongwei Li; Xulong Gao; Jiwei Jia (Cold Regions Science and Technology, 2026)

A high-voltage power corridor extraction and reconstruction method from airborne LiDAR via transmission direction and pylon localization - Yutao Zhang; Sa Li; Dandan Liu; Te Li; Juntao Yang (Advances in Space Research, 2026)

Feasibility analysis of using bacteriophage to treat acute hepatopancreatic necrosis disease in shrimp aquaculture - Hui-Yu Shih; Te-Ken Hsu; Li-Li Chen (Fish & Shellfish Immunology, 2025)

Methylene blue in electrochemical (Bio)sensing: Historical evolution, mechanistic insights, and emerging applications—A review - Li Fu; Cheng-Te Lin; Karimi-Maleh Hassan (Analytica Chimica Acta, 2025)

3D excitation-emission matrix (EEM) fluorescence-based efficient detection of cosmetics health risks: comparative AI algorithm and eXtreme Gradient Boosting (XGBoost) implementations - Runbao Du; Te Bu; Zhenchuan Huang; John Donald Morley; Yukun Xing; Meixuan Li; Hao Xu; Yuzhang Feng; Xinjie Zhou; Dan Long; Zhengyu Jin (Journal of Cleaner Production, 2025)

nUGV-1UAV robot swarms: low-altitude remote sensing-based decentralized planning framework in-field environments - Huaiqu Feng; Yudi Ruan; Dongfang Li; Te Xi; Yulei Pan; Yongwei Wang; Jun Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Spectral feature variations of low-iron olivine under intense pulse-laser irradiations - Zichen Wei; Yan Zhuang; Hao Zhang; Pengfei Zhang; Yang Li; Menghua Zhu; Te Jiang; Ronghua Pang (Icarus, 2025)

Inconsistencies in global soil moisture products and discrepancies in their relationship with vegetation productivity - Xinyao Xu; Xufeng Wang; Jingfeng Xiao; Songlin Zhang; Yanpeng Yang; Xing Li; Te Sha; Zongxing Li (Journal of Hydrology, 2025)

Enhanced deoxygenation and carbon storage in the mid-depth subarctic Pacific during the Bølling-Allerød - Qian Li; Qingping Li; Min-Te Chen; Shouwei Zhou; Jianjun Zou; Xuefa Shi (Earth and Planetary Science Letters, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

From pigment to electrocatalyst: The journey of Prussian Blue in electrochemical sensing - Li Fu; Cheng-Te Lin; Hassan Karimi-Maleh (Next Research, 2025)

Mechanisms of groundwater recovery and land subsidence mitigation in a piedmont plain - Long Zhao; Xiao-Wei Jiang; Yu-Mei Li; Yong Luo; Kun-Chao Lei; Wen-Jie Kou; Fang Tian; Miao-Zhuang Tian; Te Sha; Shu-Fang Wang; Wen-Jun Cui (Journal of Hydrology, 2025)

Biotransformation: a novel approach for the production of 6-hydroxyluteolin 7- O -methylglucuronide compound with antioxidant and anti-inflammatory potential - Chien-Yu Wu; Muddasir Khan; Hsiou-Yu Ding; Tzi-Yuan Wang; Yi-Xuan Li; Chun-Wei Liu; Jiumn-Yih Wu; Te-Sheng Chang (Natural Product Research, 2025)

The significance of organophosphate flame retardants in patients with esophageal squamous cell carcinoma - Hung-I Lu; Wan-Ting Huang; Wen-Chin Lee; Fu-Jen Cheng; Chia-Te Kung; Chin-Chou Wang; Liang-Jen Wang; Yu-Che Ou; Shau-Hsuan Li (Environmental Geochemistry and Health, 2025)

A simulation-enabled slope digital twin for real-time assessment of rain-induced landslides - Lu-Yu Ju; Te Xiao; Jian He; Wei-Fan Xu; Shi-Hao Xiao; Li-Min Zhang (Engineering Geology, 2025)

Exploring the dosimetric advantages of a novel multi-modality radiotherapy platform in prostate cancer - Jie Duan; Qinghui Yun; Zhongfei Wang; Te Zhang; Xiaohuan Sun; Hua Yang; Weiwei Li; Wei Wang; Hongfei Sun; Liting Chen; Yue Gao; Zhiwei Wei; et al. (Physical and Engineering Sciences in Medicine, 2025)

Long-term monitoring of particulate matter in an Asian community using research-grade low-cost sensors - Tzu-Chi Chieh; Shih-Chun Candice Lung; Li-Te Chang; Chun-Hu Liu; Ming-Chien Mark Tsou; Tzu-Yao Julia Wen (Environmental Monitoring and Assessment, 2025)

Surveillance and genetic diversity of bovine viral diarrhea virus in dairy herds across Taiwan - Fong-Yuan Lin; Hau-You Tzeng; Ching-Yu Tseng; Ruei-Sheng Tsai; Mami Oba; Tetsuya Mizutani; Yumiko Yamada; Hue-Ying Chiou; Shih-Te Chuang; Wei-Li Hsu (The Veterinary Journal, 2025)

A Novel Mechanical Flipper for Improving Accommodative Function in Myopic School-Age Children: A Pilot Study - Li-Te Yin; Guan-Cheng Lin; Chao-Yun Lin (Journal of Medical and Biological Engineering, 2025)

Spatial metabolomics revealed multi-organ toxicity and visualize metabolite changes induced by borneol in zebrafish - Bin Li; Chenglong Sun; Yanan Yang; Chenqinyao Li; Te Zheng; Jiashuo Zhou; Yun Zhang (Science of The Total Environment, 2025)

Development of an oral vaccine delivery system for shrimp aquaculture using attenuated Listeria monocytogenes - Jeff Chia-Kai Hsu; Te-Ken Hsu; Shuh-Bing Guan; Po-Wei Chi; Chih-Ying Chiang; Colin William Pouton; Zi-Wey Wong; Po-Yu Huang; Li-Li Chen (Aquaculture, 2025)

CD33 Ameliorates Surgery-Induced Spatial Learning and Memory Impairments Through TREM2 - Jie Zou; Yaxuan Wang; Xinyue Zhang; Xue Pan; Te Fang; Dasheng Cai; Lili Guo; Yu Li; Yi He; Xuezhao Cao (Molecular Neurobiology, 2025)

Intrasporangium zincisolvens sp. nov., A Novel Actinobacterium Isolated from Rhizosphere Soil - Lu-Yao Feng; Jiang‑Yuan Zhao; Zhu-Feng Shi; Ming‑Gang Li; Te Pu; Zhu-Li Shi; Xin Liu; Yu Wang; Le‑Le Li; Pei‑Wen Yang (Current Microbiology, 2025)

Enhanced detection of early bruises in apples using near-infrared hyperspectral imaging with geometrical influence correction for universal size adaptation - Bin Li; Te Ma; Tetsuya Inagaki; Satoru Tsuchikawa (Postharvest Biology and Technology, 2025)

Gastrointestinal dysfunction as the main performance of the oral toxicity of titanium dioxide nanoparticle on gastric ulcer rats - Yun Wang; Chen Li; Te Ba; Shengyuan Wang; Langzhi He; Zhangjian Chen; Ji Pu; Xiaoxing Cui; Guang Jia (NanoImpact, 2025)

Enhancing variety aromatic characteristics of Muscat wine through cold maceration with indigenous cryotolerant Metschnikowia pulcherrima Mp0520 - Xiqing Guo; Xueyun Zhu; Yunkai Qian; Yang Yang; Fengmei Zhu; Yue Zhao; Mingyu Zhang; Te Gao; Jun Li; Hejing Yan (Food Chemistry, 2025)

Environmental Conditions Modulate Warming Effects on Plant Litter Decomposition Globally - Sarah Schwieger; Ellen Dorrepaal; Matteo Petit Bon; Vigdis Vandvik; Elizabeth le Roux; Maria Strack; Yan Yang; Susanna Venn; Johan van den Hoogen; Fernando Valiño; Haydn J. D. Thomas; Mariska te Beest; et al. (Ecology Letters, 2025)
Empirical studies worldwide show that warming has variable effects on plant litter decomposition, leaving the overall impact of climate change on decomposition uncertain. We conducted a meta‐analysis of 109 experimental warming studies across seven continents, using natural and standardised plant material, to assess the overarching effect of warming on litter decomposition and identify potential moderating factors. We determined that at least 5.2° of warming is required for a significant increase in decomposition. Overall, warming did not have a significant effect on decomposition at a global scale. However, we found that warming reduced decomposition in warmer, low‐moisture areas, while it slightly increased decomposition in colder regions, although this increase was not significant. This is particularly relevant given the past decade's global warming trend at higher latitudes where a large proportion of terrestrial carbon is stored. Future changes in vegetation towards plants with lower litter quality, which we show were likely to be more sensitive to warming, could increase carbon release and reduce the amount of organic matter building up in the soil. Our findings highlight how the interplay between warming, environmental conditions, and litter characteristics improves predictions of warming's impact on ecosystem processes, emphasising the importance of considering context‐specific factors.

The dual role of benthic fish: Effects on water quality in the presence and absence of submerged macrophytes - Chaochao Lv; Hang Shan; Yuqing Tian; Xingchen Zhao; Zihao Wen; Chengjie Yin; Zheng Li; Haojie Su; Weijie Wang; Qingchuan Chou; Kuanyi Li; Xiaolin Zhang; et al. (Water Research, 2024)

Co-existence of airborne SARS-CoV-2 infection and non-infection in three connected zones of a restaurant - Wei Jia; Qun Wang; David Christopher Lung; Pak-To Chan; Peihua Wang; Edwin Chung-Hin Dung; Tiffany Didik; Garnet Kwan-Yue Choi; Herman Tse; Yijie Wu; Te Miao; Wenzhao Chen; et al. (Journal of Hazardous Materials, 2024)

Investigating illicit drug hotspots and daily variations using sewer-network wastewater analysis - Hank Hui-Hsiang Lin; Ming-Chi Hsieh; Jennifer Ia Wen Wen Liu; Yu-Hsiang Wang; Shu-Jie Huang; En Lien; Li-Wei Huang; Pei-Te Chiueh; Hsin-Hsin Tung; Angela Yu-Chen Lin (Chemosphere, 2024)

Maintaining KEAP1 levels in retinal pigment epithelial cells preserves their viability during prolonged exposure to artificial blue light - Ching-Hao Li; Tsung-Min Yang; Ida Fitriana; Te-Chao Fang; Liang-Huan Wu; George Hsiao; Yu-Wen Cheng (Journal of Photochemistry and Photobiology B: Biology, 2024)

To be or not to be: The fate of submerged macrophyte biodiversity in the plateau lakes after restoration for the last decade - Qingxiang Han; Junyao Sun; Qingchuan Chou; Te Cao; Wei Li; Yu Cao (Journal of Environmental Management, 2024)

Two swords combination: Smartphone-assisted ratiometric fluorescent and paper sensors for dual-mode detection of glyphosate in edible malt - Kai Deng; Haipeng Guo; Xueying Li; Te Li; Tingting Di; Runran Ma; Doudou Lei; Yining Zhang; Jiabo Wang; Weijun Kong (Food Chemistry, 2024)

Evaluation of the collapse susceptibility of loess using machine learning - Qing-yi Mu; Tian-qi Song; Zhao Lu; Te Xiao; Li-min Zhang (Transportation Geotechnics, 2024)

Wastewater-based epidemiology to monitor 68 NPS/conventional drug use in Taipei metropolitan area in Taiwan during and after COVID-19 pandemic - Te-Tien Ting; Pin-Chuan Chen; Ya-Chi Chang; Pin-Ju Chiang; Hsu-Cheng Li; Shih-Hsun Chen; Pei-Chieh Chen; Hai-Tien Chu; Ping-Yu Chuang; Yi-Hsin Liu; Pai-Shan Chen (Journal of Hazardous Materials, 2024)

Warming alters the network of physiological traits and their contribution to plant abundance - Guixiang Yuan; Eti E. Levi; Thomas A. Davidson; Torben L. Lauridsen; Martin Søndergaard; Zhenzhi Yang; Aiping Wu; Te Cao; Youzhi Li; Hui Fu; Erik Jeppesen (Science of The Total Environment, 2024)

Economic life evaluation of reservoir dams based on comprehensive costs and benefits analysis considering potential dam breach: A case study of the Luhun reservoir in China - Wei Ge; Heqiang Sun; Laihong Jing; Zongkun Li; Yongchuang Li; Bo Cao; Te Wang; Yutie Jiao; Hua Zhang; Jianyou Wang; Pieter van Gelder (Journal of Hydrology, 2024)

Determination of ochratoxin A in brown rice through a rapid, straightforward strategy based on FaTEx coupled with high-performance liquid chromatography–fluorescence detection - Li-An Wang; Te-An Kung (Food Control, 2024)

Cyclic peroxides and analogs: Antibacterial, antimalarial, and cytotoxic marine products from Xisha sponge Diacarnus sp. - Xue Leng; Hongying He; J. Enrico H. Lazaro; Xiaohui Chen; Han Ouyang; Te Li; Xia Yan; Shan He (Phytochemistry, 2024)

Epimedin B exerts an anti-inflammatory effect by regulating the MAPK/NF-κB/NOD-like receptor signalling pathways - Li Liu; Yayun Zhong; Te Zheng; Jingcheng Zhao; Shumin Ding; Jinpeng Lv; Qian Xu; Yun Zhang (Fish & Shellfish Immunology, 2024)

Exposure and health risk assessment of volatile organic compounds among drivers and passengers in long-distance buses - Jing-Jie Chen; Tiffany B. Wang; Li-Te Chang; Kai-Jen Chuang; Hsiao-Chi Chuang; Ta-Yuan Chang (Environmental Research, 2024)

Capnesterones A and B, new steroids isolated from the soft coral Capnella imbricata - Ting-Yu Cheng; Chia-Jung Yang; Po-Jen Chen; Yu-Li Chen; Bo-Rong Peng; Te-An Kung; Zhi-Hong Wen; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2024)

The effect of waste powder on the 3D printing performance of cement-based materials - Te Li; Laire Tier (Arabian Journal of Geosciences, 2024)

Spatial modelling of street-level carbon emissions with multi-source open data: A case study of Guangzhou - Yingsheng Zheng; Wenjie Li; Lu Jiang; Chao Yuan; Te Xiao; Ran Wang; Meng Cai; Haobin Hong (Urban Climate, 2024)

Three-dimensional visualization and detection of early bruise in apple based on near-infrared hyperspectral imaging coupled with geometrical influence correction - Bin Li; Te Ma; Leshang Bai; Tetsuya Inagaki; Hayato Seki; Satoru Tsuchikawa (Postharvest Biology and Technology, 2024)

Reliable sleep temperature regulation based on PMV model and dynamic thermal parameters - Zuoting Song; Yunlong Xia; Meirong Ma; Bin Deng; Te Miao; Qifeng Fan; Jilei Li (Building and Environment, 2024)

Lack of effects of eight-week left dorsolateral prefrontal theta burst stimulation on white matter macro/microstructure and connection in autism - Chun-Hung Yeh; Po-Chun Lin; Rung-Yu Tseng; Yi-Ping Chao; Chen-Te Wu; Tai-Li Chou; Rou-Shayn Chen; Susan Shur-Fen Gau; Hsing-Chang Ni; Hsiang-Yuan Lin (Brain Imaging and Behavior, 2024)

A study on siting of emergency shelters for dam failure floods considering population distribution and weather effects - Yutie Jiao; Zongkun Li; Wei Ge; Laihong Jing; Meimei Wu; Te Wang; Heqiang Sun; Jianyou Wang; Xiangyang Zhang; Pieter van Gelder (Science of The Total Environment, 2024)

Isolation and characterization of the novel phage BP14 for lysing Vibrio parahaemolyticus and reducing virulence proteins - Te-Ken Hsu; Hui-Yu Shih; Hui-Ju Huang; Jeff Chia-Kai Hsu; Han-Ching Wang; Yi-Yin Chen; Li-Li Chen (Aquaculture, 2024)

Elastoplastic damage behavior of quasi-brittle rocks considering crack closure evolution - Hongwei Li; Yuanming Lai; Mingyi Zhang; Yanyan Chen; Qinguo Ma; Te Liang; Xulong Gao (Computers and Geotechnics, 2024)

How do the growth forms of macrophytes affect the homogeneity of nearshore and open water areas? - Hang Shan; Qingchuan Chou; Chaochao Lv; Yuqing Tian; Hao Wang; Lei Shi; Zihao Wen; Weijie Wang; Xiaolin Zhang; Kuanyi Li; Leyi Ni; Te Cao (Science of The Total Environment, 2024)

Nano and phase engineering of Fe-Cu alloy exsolved perovskite oxide-based hetero-catalysts for efficient oxygen evolution reaction - Jiajia Huang; Tong Su; Huibin Zhao; Fengjiao Li; Te-Wei Chiu; Manish Singh; Qixing Wu; Liangdong Fan (Fuel, 2024)

Mechanical-Effect descriptor for oxygen reduction reaction and hydrogen evolution reaction on Single-Atomic Ni-Graphene catalysts - Wei Zhang; Fu-li Sun; Xue-long Zhang; Shuang-te Zhao; Wen-xian Chen; Gui-lin Zhuang (Fuel, 2024)

The joint association of ambient air pollution and different sleep posture with mild obstructive sleep apnea: A study conducted at Taipei Sleep Center - Yansu He; Wen-Te Liu; Shangyang Lin; Zhiyuan Li; Hong Qiu; Steve Hung Lam Yim; Hsiao-Chi Chuang; Kin Fai Ho (Science of The Total Environment, 2023)

Extraction of W, V, and As from spent SCR catalyst by alkali pressure leaching and the pressure leaching mechanism - Jinlong Liu; Chenye Wang; Xinjuan Hou; Huiquan Li; Xingrui Wang; Wenbin Hu; Te Ge; Jianbo Zhang; Ganyu Zhu; Haijiao Xie (Journal of Environmental Management, 2023)

Functions and mechanisms of sponge iron-mediated multiple metabolic processes in anaerobic ammonium oxidation - Lili Yang; Wenxuan Li; Hongjuan Zhu; Sanqiang Dong; Hao Mu; Kaiyao Hu; Te Wang; Jie Li (Bioresource Technology, 2023)

Remote sensing for chromophoric dissolved organic matter (CDOM) monitoring research 2003–2022: A bibliometric analysis based on the web of science core database - Zhihui Li; Fei Zhang; Jingchao Shi; Ngai Weng Chan; Mou Leong Tan; Hsiang-te Kung; Changjiang Liu; Chunyan Cheng; Yunfei Cai; Weiwei Wang; Xingyou Li (Marine Pollution Bulletin, 2023)

The impact of air pollution on respiratory diseases in an era of climate change: A review of the current evidence - Huan Minh Tran; Feng-Jen Tsai; Yueh-Lun Lee; Jer-Hwa Chang; Li-Te Chang; Ta-Yuan Chang; Kian Fan Chung; Han-Pin Kuo; Kang-Yun Lee; Kai-Jen Chuang; Hsiao-Chi Chuang (Science of The Total Environment, 2023)

BayLUP: A Bayesian framework for conditional random field simulation of the liquefaction-induced settlement considering statistical uncertainty and model error - Cong Miao; Zi-Jun Cao; Te Xiao; Dian-Qing Li; Wenqi Du (Gondwana Research, 2023)

Micromechanism of partial replacement of cement by glass powder and analysis of reasonable replacement rate - Te Li; Laire Tier (Arabian Journal of Geosciences, 2023)

Mechanisms of damage to sperm structure in mice on the zinc-deficient diet - Bo Sun; Jing Ma; Junsheng Liu; Yuejia Li; Jiajie Bi; Liger Te; Xin Zuo; Shusong Wang (Journal of Trace Elements in Medicine and Biology, 2023)

A novel electrochemical aptasensor based on eco-friendly synthesized titanium dioxide nanosheets and polyethyleneimine grafted reduced graphene oxide for ultrasensitive and selective detection of ciprofloxacin - Yangguang Zhu; Xiufen Li; Mengfan Wu; Mingjiao Shi; Qichen Tian; Li Fu; Hsu-Sheng Tsai; Wan-Feng Xie; Guosong Lai; Gang Wang; Nan Jiang; Chen Ye; et al. (Analytica Chimica Acta, 2023)

Enzymatic glucosylation of polyphenols using glucansucrases and branching sucrases of glycoside hydrolase family 70 - Xiaodan Li; Xiangfeng Meng; Tijn C. de Leeuw; Evelien M. te Poele; Tjaard Pijning; Lubbert Dijkhuizen; Weifeng Liu (Critical Reviews in Food Science and Nutrition, 2023)

Buffering capacity of submerged macrophytes against nutrient pulses increase with its coverage in shallow lakes - Chaochao Lv; Yuqing Tian; Liangliang Huang; Hang Shan; Qingchuan Chou; Wei Zhang; Haojie Su; Kuanyi Li; Xiaolin Zhang; Leyi Ni; Te Cao; Erik Jeppesen (Chemosphere, 2023)

Labour-saving detection of hybrid rice rows at the pollination stage based on a multi-perturbed semi-supervised model - Dongfang Li; Boliao Li; Huaiqu Feng; Te Xi; Jun Wang (Computers and Electronics in Agriculture, 2023)

Air pollution exacerbates mild obstructive sleep apnea by disrupting nocturnal changes in lower-limb body composition: a cross-sectional study conducted in urban northern Taiwan - Yansu He; Wen-Te Liu; Shang-Yang Lin; Zhiyuan Li; Hong Qiu; Steve Hung-Lam Yim; Hsiao-Chi Chuang; Kin Fai Ho (Science of The Total Environment, 2023)

Rank classification method for cascade reservoirs considering scale, benefits, and risk consequences - Te Wang; Zongkun Li; Wei Ge; Yadong Zhang; Yutie Jiao; Laihong Jing; Pieter van Gelder (Journal of Hydrology, 2023)

Numerical study on the spatial–temporal distribution of solute and salt accumulation in saturated sulfate saline soil during freezing–thawing processes: Mechanism and feedback - Jing Zhang; Yuanming Lai; Shuangyang Li; Mingyi Zhang; Zhemin You; Te Liang (Advances in Water Resources, 2023)

Organic ultraviolet filter mixture promotes bleaching of reef corals upon the threat of elevated seawater temperature - Tangtian He; Mirabelle M.P. Tsui; Anderson B. Mayfield; Pi-Jen Liu; Te-Hao Chen; Li-Hsueh Wang; Tung-Yung Fan; Paul K.S. Lam; Margaret B. Murphy (Science of The Total Environment, 2023)

Anti-inflammatory cembrane-based diterpenoids isolated from the octocoral Sinularia querciformis - Te-An Kung; Lo-Yun Chen; Chia-Ying Li; Bo-Rong Peng; Tsong-Long Hwang; Ping-Jyun Sung; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2023)

A quasi-one-dimensional bulk thermoelectrics with high performance near room temperature - Qingxin Dong; Junsen Xiang; Zhen Wang; Yunxiu Li; Rui Lu; Te Zhang; Nan Chen; Yifei Huang; Yiyan Wang; Wenliang Zhu; Guodong Li; Huaizhou Zhao; et al. (Science Bulletin, 2023)

Discovery of uncommon terpenoids from the South China Sea soft coral Sinularia scabra - Kui Wang; Jing Liu; Jian Huang; Xue Leng; Te Li; Han Ouyang; Wenhan Lin; Xia Yan; Shan He (Phytochemistry, 2023)

Data-driven landslide forecasting: Methods, data completeness, and real-time warning - Te Xiao; Li-Min Zhang (Engineering Geology, 2023)

Zinc-Deficient Diet Causes Imbalance in Zinc Homeostasis and Impaired Autophagy and Impairs Semen Quality in Mice - Bo Sun; Jing Ma; Liger Te; Xin Zuo; Junsheng Liu; Yuejia Li; Jiajie Bi; Shusong Wang (Biological Trace Element Research, 2023)

Eicosane-based thermo-conductive phase change composite for efficient capture solar energy and using in real-environment as power source - Linhong Li; Maohua Li; Yue Qin; Yapeng Chen; Wen Dai; Zhenbang Zhang; Xiangdong Kong; Ping Gong; Yandong Wang; Rongjie Yang; Bo Wang; Tao Cai; et al. (Chemical Engineering Journal, 2023)

Retrieval of soil salinity based on multi-source remote sensing data and differential transformation technology - Fei Zhang; Xingyou Li; Xiaohong Zhou; Ngai Weng Chan; Mou Leong Tan; Hsiang-Te Kung; Jingchao Shi (International Journal of Remote Sensing, 2023)

Rice seedling row detection based on morphological anchor points of rice stems - Dongfang Li; Boliao Li; Sifang Long; Huaiqu Feng; Te Xi; Shuo Kang; Jun Wang (Biosystems Engineering, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

Influence of soil infiltration and geomorphic change on main parameters of dam-break floods - Yadong Zhang; Zongkun Li; Jianyou Wang; Wei Ge; Xinyan Guo; Te Wang (Natural Hazards, 2023)

Four new cembranoids from the South China Sea soft coral Sarcophyton trocheliophorum - Lu Ren; Xue Leng; Te Li; Jing Liu; Wei Wang; Xiaojun Yan; Xia Yan; Shan He (Natural Product Research, 2023)

Rapid detection methods and modelling simulations provide new insights into cyanobacteria detection and bloom management in a tropical reservoir - Han Li; Shu Harn Te; Yasaman Tavakoli; Jingjie Zhang; Karina Yew-Hoong Gin; Yiliang He (Journal of Environmental Management, 2023)

Power laws for accurate determination of landslide volume based on high-resolution LiDAR data - Lu-Yu Ju; Li-Min Zhang; Te Xiao (Engineering Geology, 2023)

Risk assessment methods of cascade reservoir dams: a review and reflection - Te Wang; Zongkun Li; Wei Ge; Yadong Zhang; Yutie Jiao; Hua Zhang; Heqiang Sun; Pieter van Gelder (Natural Hazards, 2023)

Microscopic mechanism analysis of the influence of stone powder with different replacement ratio on concrete performance - Te Li; Laire Tier (Arabian Journal of Geosciences, 2023)

Transplantation of Nasal Olfactory Mucosa Mesenchymal Stem Cells Benefits Alzheimer’s Disease - Chun-Gu Hong; Meng-Lu Chen; Ran Duan; Xin Wang; Zhi-Lin Pang; Li-Te Ge; Ming Lu; Hui Xie; Zheng-Zhao Liu (Molecular Neurobiology, 2022)

Evaluation of the water pollution risk of dam and dike-break floods in the inundated area - Yadong Zhang; Zongkun Li; Wei Ge; Jianyou Wang; Xinyan Guo; Te Wang; Hua Zhang (Environmental Science and Pollution Research, 2022)

Currents shaped the genetic structure of Tridentiger barbatus (Günther 1861) along the Chinese coast - Jiehong Wei; Min-Yun Liu; Jen-Chieh Shiao; Fan Li; Jinquan Yang; Yoshiyuki Iizuka; Bin Kang; Ruo-Shan Tseng; Huan-Jie Shao; Te-Yu Liao (Frontiers in Marine Science, 2022)
The modern coast of China is characterized by complicated hydrology, which might be a potential factor shaping genetic structure of marine organisms. Tridentiger barbatus is a widespread benthic goby in coastal China whose range expansion might depend on larval dispersal in its spawning season. We explored the genetic structure of T. barbatus and its interrelationships with coastal currents, planktonic larval duration, and Pleistocene climate fluctuations. Genealogies of Cytb , Rh , and RAG1 reveal two lineages in T. barbatus , namely the southern and northern lineages. The southern lineage is distributed through the South China Sea to the South Yellow Sea but is absent from the North Yellow Sea and Bohai Sea. The HYCOM average flow field indicates an eddy between the North and South Yellow Seas, which might cause larval retention and limit dispersal of the southern lineage into the North Yellow Sea and the Bohai Sea. The northern lineage is distributed through the South Yellow Sea to the Bohai Sea but is absent from the South China Sea and East China Sea. The distribution of the northern lineage fits the eastward deflection of the Yellow Sea Coastal Current at the boundary of the East China Sea and South Yellow Sea, which might limit southward larval dispersal of the northern lineage into the East China Sea. We also uncovered two Cytb haplotype groups within the southern lineage, namely groups A and B, whose distributions might be shaped by the northward Taiwan Strait Current. The coincidence between the genetic structure of T. barbatus and the coastal currents and eddies strongly implies significant roles of larval dispersal and current transportation in shaping the genetic structure of T. barbatus . In addition, significant isolation by distance is found in the southern lineage, which coincides with its short planktonic larval duration (20–30 days). The inference on divergence time suggests that the observed lineages and haplotype groups in T. barbatus originated in the Pleistocene glaciations. Therefore, the coastal currents, planktonic larval duration, and historical glacial isolation are proposed as important factors shaping the genetic structure of T. barbatus .

The impacts of ambient relative humidity and temperature on supine position-related obstructive sleep apnea in adults - Wen-Te Liu; Yuan-Hung Wang; Li-Te Chang; Chih-Da Wu; Dean Wu; Cheng-Yu Tsai; Chen-Chen Lo; Kang Lo; Kian Fan Chung; Ta-Yuan Chang; Kai-Jen Chuang; Yueh-Lun Lee; et al. (Environmental Science and Pollution Research, 2022)

Not out of the woods yet: Signatures of the prolonged negative genetic consequences of a population bottleneck in a rapidly re‐expanding wader, the black‐faced spoonbill Platalea minor - Shou‐Hsien Li; Yang Liu; Chia‐Fen Yeh; Yuchen Fu; Carol K. L. Yeung; Chun‐Cheng Lee; Chi‐Cheng Chiu; Tung Hui Kuo; Fang‐Tse Chan; Yu‐Chia Chen; Wen‐Ya Ko; Cheng‐Te Yao (Molecular Ecology, 2022)
The long‐term persistence of a population which has suffered a bottleneck partly depends on how historical demographic dynamics impacted its genetic diversity and the accumulation of deleterious mutations. Here we provide genomic evidence for the genetic effect of a recent population bottleneck in the endangered black‐faced spoonbill ( Platalea minor ) after its rapid population recovery. Our data suggest that the bird's effective population size, N e , had been relatively stable (7500–9000) since 22,000 years ago; however, a recent brief yet severe bottleneck ( N e = 20) which we here estimated to occur around the 1940s wiped out >99% of its historical N e in roughly three generations. Despite a >15‐fold population recovery since 1988, we found that black‐faced spoonbill population has higher levels of inbreeding (7.4 times more runs of homozygosity) than its sister species, the royal spoonbill ( P. regia ), which is not thought to have undergone a marked population contraction. Although the two spoonbills have similar levels of genome‐wide genetic diversity, our results suggest that selection on more genes was relaxed in the black‐faced spoonbill; moreover individual black‐faced spoonbills carry more putatively deleterious mutations (Grantham's score > 50), and may therefore express more deleterious phenotypic effects than royal spoonbills. Here we demonstrate the value of using genomic indices to monitor levels of genetic erosion, inbreeding and mutation load in species with conservation concerns. To mitigate the prolonged negative genetic effect of a population bottleneck, we recommend that all possible measures should be employed to maintain population growth of a threatened species.

Machine learning-enhanced soil classification by integrating borehole and CPTU data with noise filtering - Te Xiao; Hai-Feng Zou; Ke-Sheng Yin; Yu Du; Li-Min Zhang (Bulletin of Engineering Geology and the Environment, 2021)

Influencing factors and physiochemical changes of embryogenesis through in vitro isolated microspore culture in Brassica species - Yan-Qi Dong; Yu-Hong Gao; Te Zhao; Guang-Qian Ren; Yan-Li Liu; Bin Guan; Rong-Xian Jin; Fei Gao; Yan-Li Zhang; Xiu-Fang Tan; Hong-Cai Zhu; Yu-Hong Zhang; et al. (Biologia, 2021)

Insufficient potassium and sulfur supply threaten the productivity of perennial forage grasses in smallholder farms on tropical sandy soils - Joshua Neil Monty Philp; Peter S. Cornish; Kim Sok Heng Te; Richard W. Bell; Wendy Vance; Vanndy Lim; Xueling Li; Sukanya Kamphayae; Matthew D. Denton (Plant and Soil, 2021)

Effects of cyclic variability in Pacific decadal oscillation on winter wheat production in China - Yifei Xu; Te Li; Shuanghe Shen; Guodong Xu; Abu Reza Md Towfiqul Islam; Zhenghua Hu (International Journal of Climatology, 2021)
Due to restrictions on the long period ranges of Pacific decadal oscillation (PDO) and the limited amount of winter wheat yield data in China, there is little knowledge or understanding of the effects of PDO on winter wheat production in China. To fill this knowledge gap, we simulated over 100 years of winter wheat yields using a process‐based crop model over eight locations in the dominant winter wheat‐producing area across China during 1902–2014. By using the continuous wavelet transform, we found that winter wheat yields had inter‐annual variability (4‐ and 8‐year periods) and interdecadal oscillations (22‐year and over 50‐year). The cross wavelet transform results indicated that interdecadal variations of winter wheat yields and PDO were in phase. The interdecadal variation components of PDO and winter wheat yields from 1902 to 2014 show that when PDO was in the positive (negative) phase, winter wheat yields tended to increase (decrease) by using the ensemble empirical mode decomposition (EEMD) method. The interdecadal variations of winter wheat yields were significantly associated with PDO and the mean correlation coefficient was .83. The contribution rate of PDO on winter wheat yields was approximately 11%. The interdecadal variation in winter wheat production was principally determined by the interdecadal oscillation in April precipitation and December temperature, which was modulated by the phase change of PDO. The mean correlation coefficient was −.50 and .59, respectively. This is because during the negative (positive) phase of PDO, more (less) April precipitation, and lower (higher) December temperature in the study area occur, whereas an increase in April precipitation and lower December temperature adversely affect winter wheat production. This study can aid governments and farmers to recognize the hazards of excess April precipitation and low December temperature in negative PDO years. Overall, the decadal variation in winter wheat yields due to PDO facilitates the prediction of winter wheat yields, and PDO influences crop growth by modulating large‐scale oscillation patterns.

Regional drivers of diversification in the late Quaternary in a widely distributed generalist species, the common pheasant Phasianus colchicus - Simin Liu; Yang Liu; Edouard Jelen; Mansour Alibadian; Cheng‐Te Yao; Xintong Li; Nasrin Kayvanfar; Yutao Wang; Farhad S. M. Vahidi; Jian‐Lin Han; Gombobaatar Sundev; Zhengwang Zhang; et al. (Journal of Biogeography, 2020)
Aim Pleistocene climate and associated environmental changes have influenced phylogeographic patterns of many species. These not only depend on a species’ life history but also vary regionally. Consequently, populations of widespread species that occur in several biomes might display different evolutionary trajectories. We aimed to identify regional drivers of diversification in the common pheasant, a widely distributed ecological generalist. Location Asia. Taxon Common pheasant Phasianus colchicus . Methods Using a comprehensive geographical sampling of 204 individuals from the species’ entire range genotyped at seven nuclear and two mitochondrial loci, we reconstructed spatio‐temporal diversification and demographic history of the common pheasant. We applied Bayesian phylogenetic inference to describe phylogeographic structure, generated a species tree and inferred demographic history within and migration between lineages. Moreover, to establish a taxonomic framework, we conducted a species delimitation analysis. Results The common pheasant diversified during the Late Pleistocene into eight distinct lineages. It originated at the edge of the Qinghai–Tibetan plateau and spread to East and Central Asia. Only the widely distributed lowland lineage of East Asia displayed recent range expansion. Greater phylogeographic structure was identified elsewhere, with lineages showing no sign of recent demographic changes. One lineage in south‐central China is the result of long‐term isolation within a climatically stable but topographically complex region. In lineages from arid Central Asia and China, range expansions were impeded by repeated population fragmentation during dry glacial periods and by recent aridification. Main conclusions Spatio‐temporal phylogeographic frameworks of widespread taxa such as the common pheasant provide valuable opportunities to identify divergent drivers of regional diversification. Our results suggest that diversification and population histories in the eight distinct evolutionary lineages were shaped by regionally variable effects of past climate and associated environmental changes. The evolutionary history of the common pheasant is best reflected by its being split into three species.

Incorporated maize residues will induce more accumulation of new POC in HF compared with that in LF soils: a comparison of different residue types - Yang Wang; Shuangyi Li; Yingde Xu; Ming Li; Te Shan; Weijun Zhang; Xu Liu; Muhammad Farhan Saeed; Jingkuan Wang (Journal of Soils and Sediments, 2020)

Salt tolerance of nitrate reductase in Halomonas sp. B01 - Te Wang; Yujing Li; Linghua Zhang; Weifeng Liu; Yimin Zhu (Folia Microbiologica, 2020)

A family cluster of severe acute respiratory syndrome coronavirus 2 infections - Xuesong Gao; Zheng Yuan; Di Yang; Hongjie Li; Yijin Zhang; Ping Gao; Xiaomin Liu; Wenshan Zhao; Te Xiao; Xuefei Duan (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Computational comparison of bone cement and poly aryl-ether-ether-ketone spacer in single-segment posterior lumbar interbody fusion: a pilot study - Chih-Wei Chang; Yu-Hsuan Chung; Chia-Jung Chang; Yen-Nien Chen; Chun-Ting Li; Chih-Han Chang; Yao-Te Peng (Physical and Engineering Sciences in Medicine, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Asperfurandiones A and B, two antifungal furandione analogs from a marine-derived fungus Aspergillus versicolor - Lijian Ding; Peng Xu; Te Li; Xiaojian Liao; Shan He; Shihai Xu (Natural Product Research, 2019)

Dynamics of maize straw–derived nitrogen in soil aggregates as affected by fertilization - Yang Wang; Ming Li; Jiubo Pei; Tingting An; Muhammad Farhan Saeed; Te Shan; Yingde Xu; Jingkuan Wang (Journal of Soils and Sediments, 2019)

Regulation of myostatin expression is associated with growth and muscle development in commercial broiler and DMC muscle - Tengfei Dou; Zhengtian Li; Kun Wang; Lixian Liu; Hua Rong; Zhiqiang Xu; Ying Huang; Dahai Gu; Xiaobo Chen; Wenyuan Hu; Jiarong Zhang; Sumei Zhao; et al. (Molecular Biology Reports, 2018)

Impact of Land Use Change on Hydrologic Processes in a Large Plain Irrigation District - Xiao-Bo Luan; Pu-Te Wu; Shi-Kun Sun; Xiao-Lei Li; Yu-Bao Wang; Xue-Rui Gao (Water Resources Management, 2018)

Community responses to dam removal in a subtropical mountainous stream - Hao-Yen Chang; Ming-Chih Chiu; Yi-Li Chuang; Chyng-Shyan Tzeng; Mei-Hwa Kuo; Chao-Hsien Yeh; Hsiao-Wen Wang; Sheng-Hai Wu; Wen-Hui Kuan; Shang-Te Tsai; Kwang-Tsao Shao; Hsing-Juh Lin (Aquatic Sciences, 2017)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

The involvement of supratentorial white matter in multiple system atrophy: a diffusion tensor imaging tractography study - Po-Shan Wang; Chien-Li Yeh; Chia-Feng Lu; Hsiu-Mei Wu; Bing-Wen Soong; Yu-Te Wu (Acta Neurologica Belgica, 2017)

Assessment of different route choice on commuters’ exposure to air pollution in Taipei, Taiwan - Hsien-Chih Li; Pei-Te Chiueh; Shi-Ping Liu; Yu-Yang Huang (Environmental Science and Pollution Research, 2017)

Forelimb contractures and abnormal tendon collagen fibrillogenesis in fibulin-4 null mice - Dessislava Z. Markova; Te-Cheng Pan; Rui-Zhu Zhang; Guiyun Zhang; Takako Sasaki; Machiko Arita; David E. Birk; Mon-Li Chu (Cell and Tissue Research, 2016)

Enhancement of random finite element method in reliability analysis and risk assessment of soil slopes using Subset Simulation - Dian-Qing Li; Te Xiao; Zi-Jun Cao; Chuang-Bing Zhou; Li-Min Zhang (Landslides, 2016)

PPR protein PDM1/SEL1 is involved in RNA editing and splicing of plastid genes in Arabidopsis thaliana - Hong-Dao Zhang; Yong-Lan Cui; Chao Huang; Qian-Qian Yin; Xue-Mei Qin; Te Xu; Xiao-Fang He; Yi Zhang; Zi-Ran Li; Zhong-Nan Yang (Photosynthesis Research, 2015)

Ground-dwelling arthropod community response to native grassland conversion in a temperate desert of northwestern China - Qi Feng; Feng-Rui Li; Ji-Liang Liu; Te-Sheng Sun; Li-Juan Chen (Journal of Insect Conservation, 2015)

The influence of natural and human factors in the shrinking of the Ebinur Lake, Xinjiang, China, during the 1972–2013 period - Fei Zhang; Tashpolat Tiyip; Verner Carl Johnson; Hsiang-te Kung; Jian-li Ding; Qian Sun; Mei Zhou; Ardak Kelimu; Ilyas Nurmuhammat; Ngai Weng Chan (Environmental Monitoring and Assessment, 2015)

Species delimitation in the C hinese bamboo partridge B ambusicola thoracica ( P hasianidae; A ves) - Chih‐Ming Hung; Hsin‐Yi Hung; Chia‐Fen Yeh; Yi‐Qiang Fu; De Chen; Fumin Lei; Cheng‐Te Yao; Chiou‐Ju Yao; Xiao‐Jun Yang; Yu‐Ting Lai; Shou‐Hsien Li (Zoologica Scripta, 2014)
Although tropical and subtropical Asia harbour a high level of species diversity, their species richness can be underestimated because species which are in fact distinct have not been separately identified. In this study, we delimit B ambusicola thoracica into two full species, the Chinese bamboo partridge ( B. thoracica ) in continental Asia and the Taiwanese bamboo partridge ( B . sonorivox ) on the island of Taiwan, using coalescent‐based multilocus division and diagnosable vocalization patterns. Isolation‐with‐migration analysis indicated that the two bamboo partridges diverged approximately 1.8 million years ago, with gene flow present most probably during the early stages of their divergence. This conclusion supports the hypothesis that diverging lowland lineages spread across the Asian mainland, and continental islands have more opportunities for secondary contact than highland ones when the sea level was low. Our results imply that conservation of biodiversity in tropical and subtropical Asia could be hindered by overlooking numerous ‘hidden’ species and highlight the importance of re‐examining the taxonomic statuses of species in this region traditionally defined as polytypic.

Selection and characterization of an acid-resistant mutant of serotype O foot-and-mouth disease virus - Te Liang; Decheng Yang; Mengmeng Liu; Chao Sun; Fang Wang; Jingfei Wang; Haiwei Wang; Shanshan Song; Guohui Zhou; Li Yu (Archives of Virology, 2014)

Converting natural vegetation to farmland alters functional structure of ground-dwelling beetles and spiders in a desert oasis - Feng-Rui Li; Ji-Liang Liu; Te-Sheng Sun; Bo-Wen Jin; Li-Juan Chen (Journal of Insect Conservation, 2014)

Effects of drip irrigation on deep root distribution, rooting depth, and soil water profile of jujube in a semiarid region - Li-hui Ma; Xiao-li Liu; You-ke Wang; Pu-te Wu (Plant and Soil, 2013)

Effects of the Conversion of Native Vegetation to Farmlands on Soil Microarthropod Biodiversity and Ecosystem Functioning in a Desert Oasis - Feng-Rui Li; Qi Feng; Ji-Liang Liu; Te-Sheng Sun; Wei Ren; Zhen-Huan Guan (Ecosystems, 2013)

An empirical comparison of character‐based and coalescent‐based approaches to species delimitation in a young avian complex - Bailey D. McKay; Herman L. Mays; Yuchun Wu; Hui Li; Cheng‐te Yao; Isao Nishiumi; Fasheng Zou (Molecular Ecology, 2013)
The process of discovering species is a fundamental responsibility of systematics. Recently, there has been a growing interest in coalescent‐based methods of species delimitation aimed at objectively identifying species early in the divergence process. However, few empirical studies have compared these new methods with character‐based approaches for discovering species. In this study, we applied both a character‐based and a coalescent‐based approaches to delimit species in a closely related avian complex, the light‐vented/Taiwan bulbul ( P ycnonotus sinensis / P ycnonotus taivanus ). Population aggregation analyses of plumage, mitochondrial and 13 nuclear intron character data sets produced conflicting species hypotheses with plumage data suggesting three species, mitochondrial data suggesting two species, and nuclear intron data suggesting one species. Such conflict is expected among recently diverged species, and by integrating all sources of data, we delimited three species verified with independently congruent character evidence as well as a more weakly supported fourth species identified by a single character. Attempts to validate species hypothesis using B ayesian P hylogenetics and P hylogeography ( BPP ), a coalescent‐based method of species delimitation, revealed several issues that can seemingly affect statistical support for species recognition. We found that θ priors had a dramatic impact on speciation probabilities, with lower values consistently favouring splitting and higher values consistently favouring lumping. More resolved guide trees also resulted in overall higher speciation probabilities. Finally, we found suggestive evidence that BPP is sensitive to the divergent effects of nonrandom mating caused by intraspecific processes such as isolation‐with‐distance, and therefore, BPP may not be a conservative method for delimiting independently evolving population lineages. Based on these concerns, we questioned the reliability of BPP results and based our conclusions about species limits exclusively on character data.

Differential Legionella spp. survival between intracellular and extracellular forms in thermal spring environments - Po-Min Kao; Min-Che Tung; Bing-Mu Hsu; Shih-Yung Hsu; Jen-Te Huang; Jorn-Hon Liu; Yu-Li Huang (Environmental Science and Pollution Research, 2013)

Biomechanical features of eccentric cambial growth and reaction wood formation in broadleaf tree branches - Ching-Chu Tsai; Li-Fen Hung; Ching-Te Chien; Shiang-Jiuun Chen; Yan-San Huang; Ling-Long Kuo-Huang (Trees, 2012)

Ds transposon is biased towards providing splice donor sites for exonization in transgenic tobacco - Kuo-Chan Huang; Hsiu-Chun Yang; Kuan-Te Li; Li-yu Daisy Liu; Yuh-Chyang Charng (Plant Molecular Biology, 2012)

Concentrations of polycyclic aromatic hydrocarbon in the surface sediments from inter-tidal areas of Kenting coast, Taiwan - Jing-O Cheng; Fung-Chi Ko; Jan-Jung Li; Te-Hao Chen; Ying-Ming Cheng; Chon-Lin Lee (Environmental Monitoring and Assessment, 2012)

Spatial distribution of roots in a dense jujube plantation in the semiarid hilly region of the Chinese Loess Plateau - Li-hui Ma; Pu-te Wu; You-ke Wang (Plant and Soil, 2012)

Eicosadienoic acid differentially modulates production of pro-inflammatory modulators in murine macrophages - Yung-Sheng Huang; Wen-Cheng Huang; Chi-Wei Li; Lu-Te Chuang (Molecular and Cellular Biochemistry, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

Prostaglandin I2 analogues suppress TNF-α expression in human monocytes via mitogen-activated protein kinase pathway - Wei-Li Wang; Chang-Hung Kuo; Yu-Te Chu; Ching-Hua Huang; Ka-Pan Lam; Shau-Ku Huang; Yuh-Jyh Jong; Yu-Ting Kuo; Chih-Hsing Hung (Inflammation Research, 2011)

Effects of PGI2 analogues on Th1- and Th2-related chemokines in monocytes via epigenetic regulation - Chang-Hung Kuo; Ying-Chin Ko; San-Nan Yang; Yu-Te Chu; Wei-Li Wang; Shau-Ku Huang; Huan-Nan Chen; Wan-Ju Wei; Yuh-Jyh Jong; Chih-Hsing Hung (Journal of Molecular Medicine, 2011)

α-Mangostin Suppresses Phorbol 12-myristate 13-acetate-Induced MMP-2/MMP-9 Expressions via αvβ3 Integrin/FAK/ERK and NF-κB Signaling Pathway in Human Lung Adenocarcinoma A549 Cells - Yuan-Wei Shih; Shang-Tao Chien; Pin-Shern Chen; Jian-Hui Lee; Shu-Hau Wu; Li-Te Yin (Cell Biochemistry and Biophysics, 2010)

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Acacetin, a flavonoid, inhibits the invasion and migration of human prostate cancer DU145 cells via inactivation of the p38 MAPK signaling pathway - Kun-Hung Shen; Shun-Hsing Hung; Li-Te Yin; Chun-Shui Huang; Chang-Hung Chao; Chein-Liang Liu; Yuan-Wei Shih (Molecular and Cellular Biochemistry, 2010)

Isolation and characterization of 23 microsatellite loci in the black-faced spoonbill (Platalea minor) and amplification in other Ciconiiformes waterbirds - Carol K. L. Yeung; Yu-Cheng Hsu; Cheng-Te Yao; Shou-Hsien Li (Conservation Genetics, 2009)

Single-Trial Analysis of Cortical Oscillatory Activities During Voluntary Movements Using Empirical Mode Decomposition (EMD)-Based Spatiotemporal Approach - Po-Lei Lee; Li-Zen Shang; Yu-Te Wu; Chih-Hung Shu; Jen-Chuen Hsieh; Yung-Yang Lin; Chi-Hsun Wu; Yu-Lu Liu; Chia-Yen Yang; Chia-Wei Sun; Kuo-Kai Shyu (Annals of Biomedical Engineering, 2009)

Sensory Acquisition in the Cerebellum: An fMRI Study of Cerebrocerebellar Interaction During Visual Duration Discrimination - Lynn Y. L. Shih; Li-Fen Chen; Wen-Jui Kuo; Tzu-Chen Yeh; Yu-Te Wu; Ovid J. L. Tzeng; Jen-Chuen Hsieh (The Cerebellum, 2009)

Physiological Stress of High NH 4 + Concentration in Water Column on the Submersed Macrophyte Vallisneria Natans L. - Te Cao; Ping Xie; Zhongqiang Li; Leyi Ni; Meng Zhang; Jun Xu (Bulletin of Environmental Contamination and Toxicology, 2009)

A study of NO trafficking from dinitrosyl–iron complexes to the recombinant E. coli transcriptional factor SoxR - Feng-Chun Lo; Chang-Li Chen; Chien-Ming Lee; Ming-Che Tsai; Tsai-Te Lu; Wen-Feng Liaw; Steve S.-F. Yu (JBIC Journal of Biological Inorganic Chemistry, 2008)

Distribution of DDT in a Typical DDT Waste Contaminated Site - Wenbin Liu; Changliang Li; Minghui Zheng; Li Wang; Sumei Li; Te Ba; Guijin Su; Lirong Gao; Lifei Zhang (Bulletin of Environmental Contamination and Toxicology, 2008)

Localization and Mutation Detection for Paroxysmal Kinesigenic Choreoathetosis - Te Du; Bin Feng; Xin Wang; Wei Mao; Xilin Zhu; Liping Li; Bei Sun; Nifang Niu; Yang Liu; Yuping Wang; Biao Chen; Xingqiu Cai; et al. (Journal of Molecular Neuroscience, 2008)

Association of Heart Rate Variability of the Elderly with Personal Exposure to PM1, PM1–2.5, and PM2.5–10 - Li-Te Chang; Chin-Sheng Tang; Ying-Zu Pan; Chang-Chuan Chan (Bulletin of Environmental Contamination and Toxicology, 2007)

Msh3 is a limiting factor in the formation of intergenerational CTG expansions in DM1 transgenic mice - Laurent Foiry; Li Dong; Cédric Savouret; Laurence Hubert; Hein te Riele; Claudine Junien; Geneviève Gourdon (Human Genetics, 2006)

A homozygous COL6A2 intron mutation causes in-frame triple-helical deletion and nonsense-mediated mRNA decay in a patient with Ullrich congenital muscular dystrophy - Laura Lucarini; Betti Giusti; Rui-Zhu Zhang; Te-Cheng Pan; Cecilia Jimenez-Mallebrera; Eugenio Mercuri; Francesco Muntoni; Guglielmina Pepe; Mon-Li Chu (Human Genetics, 2005)

Recognition of Motor Imagery Electroencephalography Using Independent Component Analysis and Machine Classifiers - Chih-I Hung; Po-Lei Lee; Yu-Te Wu; Li-Fen Chen; Tzu-Chen Yeh; Jen-Chuen Hsieh (Annals of Biomedical Engineering, 2005)

Characterizinig Precipitation Chemistry in Changhua, Central Taiwan Using Weather Conditions And Multivariate Analysis - Chuan-Te Chang; Teng-Chiu Lin; Mei-Li Hsueh (Water, Air, & Soil Pollution, 2005)

Variation of xylanosomal subunit composition of Streptomyces olivaceoviridis by nitrogen sources - Wei Deng; Zheng-Qiang Jiang; Li-Te Li; Yun Wei; Bo Shi; Isao Kusakabe (Biotechnology Letters, 2005)

A novel, ultra-large xylanolytic complex (xylanosome) secreted by Streptomyces olivaceoviridis - Zheng-Qiang Jiang; Wei Deng; Li-Te Li; Chang-He Ding; Isao Kusakabe; Sze-Sze Tan (Biotechnology Letters, 2004)